Efficient land configurations and nutrient management in Bt cotton (Gossypium herbaceum) - KUMARI, CH PRAGATHI; DEVI, K B SUNEETHA; REKHA, K BHANU; SRIDEVI, S; REDDY, S NARENDER (The Indian Journal of Agricultural Sciences, 2023)
Field experiments were conducted during rainy (kharif) season, 2015 and 2016 to assess the impact of land configurations and nutrient management on Bt cotton (Gossypium herbaceum L.) at College Farm, College of Agriculture, Rajendranagar, Professor JayashankarTelangana State Agricultural University, Hyderabad, Telangana. Treatments consisted of four land configurations, viz. flat bed sowing, ridge and furrow, broad bed and furrow (BBF) and BBF laid with poly mulch as main plots and five nutrient management treatments in sub plots, viz. farmer’s practice, 100% RDF-150:60:60 NPK kg/ha, 125% RDF, 100% RDF along with 25% N through farmyard manure and 100% RDF along with 25% N through pressmud laid out in triplicated strip plot design. Results revealed that yield attributes (bolls per plant and boll weight), seed cotton yield and field water use efficiency were significantly higher with BBF with poly mulch along with application of 100% RDF + 25% RDN through organics (pressmud or FYM) comparable to BBF laid with poly mulch and application of 125% RDF through inorganics. Soil moisture extraction by crop was higher from 0–15 cm and 15–30 cm depth in poly mulch + BBF over other land configurations.